1995
DOI: 10.1016/s0960-9822(95)00180-1
|View full text |Cite
|
Sign up to set email alerts
|

How does taxol stabilize microtubules?

Abstract: As in another recent investigation using guanylyl-(alpha,beta)-methylene-diphosphonate (a non-hydrolyzable GTP analogue), microtubule stabilization with taxol is accompanied by a conformational change in the microtubule surface lattice and, implicitly, in the tubulin dimer. We speculate that a general mechanism may underlie the stabilization of microtubules by different agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
164
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(186 citation statements)
references
References 33 publications
20
164
1
1
Order By: Relevance
“…Although one difference between our studies was in the ionic strength of the buffers, we also noted that a potentially important difference between the two studies was that we used GMPCPPstabilized microtubules to analyze acetylation patterns on preformed microtubules, whereas Szyk et al (18) used Taxol-stabilized microtubules. Both the timing and method of Taxol introduction have been shown to affect the structure of Taxol microtubules (34). Our work has demonstrated that microtubule structure, and particularly the presence of defects and openings in the microtubule lattice, would have a substantial impact on the efficiency of αTAT1 in accessing and acetylating luminal acetylation sites.…”
Section: Discussionmentioning
confidence: 79%
“…Although one difference between our studies was in the ionic strength of the buffers, we also noted that a potentially important difference between the two studies was that we used GMPCPPstabilized microtubules to analyze acetylation patterns on preformed microtubules, whereas Szyk et al (18) used Taxol-stabilized microtubules. Both the timing and method of Taxol introduction have been shown to affect the structure of Taxol microtubules (34). Our work has demonstrated that microtubule structure, and particularly the presence of defects and openings in the microtubule lattice, would have a substantial impact on the efficiency of αTAT1 in accessing and acetylating luminal acetylation sites.…”
Section: Discussionmentioning
confidence: 79%
“…These consist of (i) an inward displacement in Taxol microtubules of the maxima of the J 0 Bessel function (corresponding to the low resolution transform of the excess electron density of the microtubule hollow cylinders), which serves to measure the different mean diameter (protofilament number) of each microtubule population and (ii) a small inward displacement of the J n and J n-3 Bessel function maxima in both types of taxoid induced microtubules with respect to glycerol microtubules (27,28). The latter is compatible with an increase in the spacing between tubulin monomers along the microtubule protofilament (38,39).…”
Section: Fig 4 Changes In Microtubule Protofilament Number Induced mentioning
confidence: 87%
“…The number of protofilaments corresponding to each image in this work were classified from the type of fringe pattern (27,51). This method has been widely employed (28,39,52,53). In addition, the orientation of the moiré fringe patterns in cryoelectron micrographs allows determination of microtubule polarity (54).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that there were soluble pools of tubulin sequestered and maintained in a temporary 'oligomeric' state, which retained assembling and disassembling potential (Liu & Lessman 2007). Upon exposure to microtubule promoting or destabilizing factors (such as g-tubulin, paclitaxel, or colchicines) (Arnal & Wade 1995;Amos & Löwe 1999;Casalou et al 2001;Raynaud-Messina & Merdes 2007), microtubules were observed to begin assembling or disassembling. It was also determined that after extraction and denaturation in boiling water, the a/b-tubulin dimer was depolymerized and a-tubulin was observed only in the supernatant.…”
Section: Biochemical Characterization Of A- G- and D-tubulinsmentioning
confidence: 99%